Development and perceived usability of 3D-model PlasmaMesh as a teaching aid for subtopics in plasma membrane - Cheng, Lee Hoong (Tanjong Malim, 2024)
Development and perceived usability of 3D-model PlasmaMesh as a teaching aid for subtopics in plasma membrane by Cheng, Lee Hoong